Various presentations of cutaneous tuberculosis at a tertiary care centre: a one year prospective study - Jayanthi, N. S.; Anandan, V.; Kopika, S. (International Journal of Research in Dermatology, 2018)
Background: Cutaneous tuberculosis is a rare manifestation of tuberculosis accounting for about 1.5% of all the extra pulmonary manifestations, though the prevalence of pulmonary tuberculosis is high in India. The aim of the study was to prospectively analyze the various clinical presentations of cutaneous TB and their age and sex distribution among the OPD attending patients over a period of one year. Methods: Prospective study, conducted during July 2016 to June 2017. Clinically suspected cases of cutaneous tuberculosis were subjected to lesional biopsy and the results obtained were analyzed. Results: Out of 36 clinically suspected cases, 24 turned out to be cutaneous tuberculosis and apart from these, 5 cases were referred from other departments as cutaneous tuberculosis. The predominant presentation was lupus vulgaris in 12 patients, followed by tuberculous verrucosa cutis in 8 cases, tuberculous ulcers in 3 cases and the remaining 2 cases were erythema induratum of Bazin. Among them, 13 were men accounting to about 52% and 7 were children which accounted for 28% and the remaining 5 were women which added to 20%. Conclusions: Though the cutaneous manifestations of tuberculosis is very rare, the recent years have shown a rising incidence especially among children and therefore requires a high index of suspicion in them since India has very high prevalence of tuberculosis as such.